The Architecture of Traditional and Modern Afghan Houses and the Fundamentalist Regime: Impacts on Women's Lives - Sayed Abdul Basir Samimi; Artur Simões Rozestraten; Júnia Aparecida Laia da Mata (Malala)
This research investigates the relation between the architectural attributes of traditional and modern houses in Afghanistan and the constraints imposed on Afghan women’s lives by considering recent incidents. This study draws upon a combination of historical sources and news articles pertaining to contemporary Afghan affairs as its primary data sources. Additionally, it comparatively analyzes two houses — one exemplifying the traditional Afghan design and another, modern architecture — in the City of Herat, Afghanistan. By highlighting the interplay between architectural features and their implications for women’s lives, this research aims to shed light on this dwelling relationship. The findings of this research indicate that urban areas more conspicuously manifest modernization in physical aspects, evinced by the prevalence of modern residential houses. However, with the initiation of new restrictions imposed by the Taliban after 2021, modern houses (characterized by more limited open spaces than traditional ones) engender heightened vulnerability for Afghan women. Thus, confining women within these modern houses deleteriously impacts their physical and mental well-being.